Biochemical blood parameters of broiler chickens when using a siliceous rock additive - opoka in feeding - Nagimova, G. Kh.; Montaeva, N. S.; Kеrеyеv, А. K. (Ғылым және білім=Наука и образование=Science and education. - 2024. - 2-1 (75). Ч. І. - Р. 296-303, 2024)
Understanding the digestive system and metabolic processes of broiler chickens is essential for optimizing productivity in poultry farming. Adequate energy and nutrient intake are necessary for maintaining life and enhancing productivity. Monitoring basic blood parameters can provide valuable insights into the overall health and immune function of the birds, as changes in protein composition are indicative of growth and development processes. The research was conducted on Ross-308 cross broiler chickens following a scientific and economic experiment design. Three groups were established: one control group and two experimental groups, each consisting of 50 birds. The experimental groups were comprised of day-old broiler chickens fed according to the cross's dietary recommendations. Our findings indicate that supplementing the main diet of broiler chickens with a mineral additive - opoka, while maintaining the nutritional value of protein and amino acids, positively impacted the blood protein profile, leading to increased total protein levels and its fractions. There were no significant differences in the biochemical parameters of blood serum between the experimental and control groups, demonstrating the safety and effectiveness of incorporating the mineral feed additive siliceous rock - opoka in broiler chicken diets.
Keywords: журнал кокснво; ветеринария; poultry farming; broiler chickens; opoka; blood; serum; albumins; globulins; hemoglobin; erythrocytes; leukocytes; protein; птицеводство; пищеварение птиц; метаболизм; минеральные вещества; опока; минеральные добавки; бройлеры; кормление птиц; ЗКАТУ